Estimation of the quantitative needs for air conditioning using the temperature and humidity index (THI) and the wind cooling index (Ko) for stations(Ramadi, Ana, Rutba) - Ali sleman Arzeek (Thi Qar Arts Journal, 2025)
God Almighty has given man a body that can maintain his constant temperature (skin temperature) (33°C), but this value varies in unusual circumstances through a number of processes by which the body releases heat or acquires it. It has to increase the process of sweating to keep the body from high heat, or it may get cold by contacting another body that is colder than it. This study aimed to apply climatic evidence (temperature-humidity (THI, wind cooling), in order to estimate the population's needs for heating and cooling purposes in the (Ramadi, Ana, Rutba) stations in order for the residents of those districts to reach the greatest degree of comfort. The results of applying the temperature-humidity index equation (THI) came during the winter season in the study stations (Ramadi, Ana, Rutba) with the climate being (warm relative comfort) but during the summer (June, July, August). It was characterized by being (extremely disturbed, meaning 100% of individuals feel discomfort) While the results of applying the equation of daytime wind cooling for wind cooling for the winter season in Al-Ramadi station (it tends to be cold) while it is (it tends to be cold) in my stations (Anah, humid). Hot) and for all summer months (June-July-August).